PERENCANAAN PENINGKATAN FLOOD SHELTER DI DAERAH ALIRAN SUNGAI BERINGIN SEMARANG - Siti Nuriskha Amalia; Annisa Khizamatul F.U.; Suharyanto Suharyanto; Dwi Kurniani (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Flood is one of the disaster which happened in Semarang City. Many negative impact arising from flood disaster, such as loss of victim or material. One of the handling solution is developed flood shelter, make a group of disaster preparedness and early warning system. Identification location of flood shelter are in Beringin Watershed Semarang which consists of 6 Village, namely Wates Village, Wonosari Village, Mangunharjo Village, Mangkang Wetan Village, Gondorio Village, and Beringin Village. Data obtained from the field surve with existing data of flood shelter that has been there. Sources of criteria and terms for flood shelter location are sphere project 2011, Health Minister’s decision and regulations of BPBD.Tool support early warning system used is AWLR (Automatic Water Lever Recorder) and ARR (Automatic Rain Recorder) is placed in the Wates Village. To complete the shortage of space, the Wonosari Village established in the form of building houses on stilts and emergency stairs because it has cliffs that lead to delays in evacuation and treatmen, while other villages for each flood shelters set up tents with size (14x6) meter. Participation and public awareness around the riverbanks to keep clean is needed, so flooding can be reduced.